Effect of voltage step constraint and load models in optimal location and size of distributed generation - Payasi R.P.; Singh A.K.; Singh D. (My University, 2025)
The distributed generation planning (DGP) in distribution system is affected with load models. Further, The size of distributed generation is also affected with voltage step constraints. In previous works, the effects of load models and voltage step constraint, in distributed generation planning (DGP), have not been studied together by the researchers so for. In this paper, voltage step constraint, along with usual constraints i.e. bus voltage limits and line capacity limits, and basic load models have been considered in DGP. The study has been carried out in 38 bus test system using incremental power flow and exhaustive search method. The results show that optimal location and size along with intake power from grid are significantly affected by voltage step constraint and load models. © 2013 IEEE.